A Brief Analysis on Error in Indonesian Beginner Level Students’ Chinese Composition - Rosalin, Kelly (Bina Nusantara University, 2014)
Indonesian Chinese students at beginner level often encounter difficulties in writing. Qualitative research is used in this article, through the collection of midterm essays from first-year Binus University students, the author classified students? error in writing into some categories, and analyzed them to help teachers and students during the Chinese Writing Class. During the Chinese writing learning process research found out that there are errors occur in wrong usage of word usage, punctuation, Chinese character writing, and the error of addition, omission, ordering, and selection are commonly found in grammatical errors.